Tributyl borate as a novel electrolyte additive to improve high voltage stability of lithium cobalt oxide in carbonate-based electrolyte - Qin, Zhaoming; Hong, Bo; Duan, Boyu; Hong, Shu; Chen, Yuncai; Lai, Yanqing; Feng, Jiang (Elsevier, 2018)
Tributyl borate is used as a novel electrolyte additive to improve the stability of LiCoO2 cathode operating at a high charging-cutoff voltage. The HOMO energy calculation notes that Tributyl borate would be preferentially oxidized and then generate a more uniform, extremely stable, and lower resistance cathode solid electrolyte interphase (CEI) on the LiCoO2 surface. This CEI film can effectively suppress the subsequent decomposition of electrolyte and improve cyclic stability and discharge capability of LiCoO2 cathode. With the electrolyte contained 0.5 wt.% tributyl borate, the LiCoO2/Li cells achieve a capacity retention of 85.2% after 120 cycles at 3.0–4.4 V, comparing to the capacity retention of 37.7% for the cells without tributyl borate.